1999
DOI: 10.1007/s001250051275
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in glutamic acid decarboxylase expression among single rat pancreatic beta cells

Abstract: Pancreatic beta cells contain the enzyme glutamic acid decarboxylase (GAD) that catalyses the biosynthesis of the neurotransmitter g-aminobutyric acid (GABA) [1,2]. Two non-allelic genes probably derived from a common ancestral gene encode GAD. The two GAD isoforms, named GAD65 and GAD67 according to their approximate molecular weight in kDa, share a similar structure, except in the first 95 amino acids [3]. Despite their homology, there are structural and functional differences between them that are reflected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
(34 reference statements)
0
10
0
3
Order By: Relevance
“…In humans, the rate of GAD expression is increased in pancreatic ␤-cells at the postnatal stage but is decreased in adulthood (46). Similarly, the expression of GAD in the islets of adult rats is probably at a maximal level and thus was used as a marker of ␤-cell maturity in rats (47). Taken together, the rate of GAD expression in ␤-cells seems to be correlated with age-dependent ␤-cell maturation.…”
Section: Discussionmentioning
confidence: 91%
“…In humans, the rate of GAD expression is increased in pancreatic ␤-cells at the postnatal stage but is decreased in adulthood (46). Similarly, the expression of GAD in the islets of adult rats is probably at a maximal level and thus was used as a marker of ␤-cell maturity in rats (47). Taken together, the rate of GAD expression in ␤-cells seems to be correlated with age-dependent ␤-cell maturation.…”
Section: Discussionmentioning
confidence: 91%
“…Анализ результатов этих исследований на моделях животных и у человека позво лил выявить такие потенциально важные антигены, как инсулин, глютаминовая кислота декарбоксилазы (GAD) и тирозинфосфотаза протеина IA-2, гликопротеиды (ганг-лиозид Gm2-1), а также такие компоненты клеток, как ту-булин и актин [14,25,35,39].…”
Section: гуморальные нарушенияunclassified
“…Среди популяции Р-клеток обнаружены большие клет ки, образующие бляшки, которые отвечают за большую часть секретируемого инсулина и представляют самый низкий порог его секреции в ответ на изменения внекле точных концентраций глюкозы [21,39]. Эта субпопуляция Р-клеток, обеспечивающая высокий уровень секреции ин сулина, была названа LP-клетками.…”
Section: гуморальные нарушенияunclassified
See 1 more Smart Citation
“…Degli et al suggested that accumulation of glutamate upon perturbation of GABA network, produced by nutrient or environmental stress, could up-regulate expression of GAD [17]. High glucose concentrations were also shown to increase GAD expression in cultured islets [18][19][20]. GAD expression varies also during ontogeny.…”
Section: Introductionmentioning
confidence: 99%